Physical activity and nutrition behavioural outcomes of a home-based intervention program for seniors : a randomized controlled trial - Burke, Linda. (2013)
Background: This intervention aimed to ascertain whether a low-cost, accessible, physical activity and nutrition program could improve physical activity and nutrition behaviours of insufficiently active 60–70 year olds residing in Perth, Australia.